Meaning of Developing Student Centered Classroom Environment - Harjali, Harjali (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
Classroom learning environment has been widely researched topics in elementary and secondary education. This study aimed to investigate teachers’ experience in building classroom learning environment. This research involved a qualitative phenomenological design that employed a purposeful sample of teachers at Junior High School Classrooms in Ponorogo. Data were collected via in depth interviews and participant observations. In analyzing the data, the writer evaluated the interview transcriptions and the observation field notes which were organized into relevant themes (Cresswell, 2009). Most of the participants suggest that there were some meanings gotten from building students center classrooms learning environment based on constructivistics paradigm. Classroom learning environment is built psychologically and socio-culturally context. Thus students can manage, interact, and achieve their learning objectives, facilitated by learning activities based on selected materials, strategies, and media